Analysis and Dynamic Stabilization of a High-Voltage VSC-MTDC Grid With DC Power Flow Controller Connected to Extremely Weak AC Systems - Hassanien Ramadan A. Mohamed; Yasser Abdel-Rady I. Mohamed; Ehab F. El-Saadany (IEEE Open Journal of Power Electronics, 2024)
The high-voltage voltage-source converter (VSC)-based multi-terminal dc (MTDC) grid is a key technology for integrating offshore wind energy and enabling bulk power transmission across nations and continents. This paper addresses the small-signal stability of an MTDC grid equipped with a power flow controller (PFC) under extremely weak ac system interconnections. Using a comprehensive linearized state-space model, eigenvalue analysis uncovers that beyond the well-documented low-frequency oscillations (LFO), an MTDC grid may experience unstable medium-frequency oscillations (MFO) under rectifier operation of droop voltage-controlled VSCs when interfaced to an extremely weak ac system. Moreover, it was shown that the most challenging scenario is when multiple droop voltage-controlled VSCs are interfaced to very weak ac systems, with unstable LFO and MFO observed at short-circuit ratio values of 1.4 and 1.8, respectively. Sensitivity analysis is conducted to assess the impact of the droop voltage control gains, PFC control parameters, and dc breaker reactor on the system dominant eigenmodes in such critical weak conditions. Simple yet efficient LFO and MFO compensators are proposed to stabilize the system, and their parameters design was detailed. Extensive simulation studies and real-time validation tests verify the analytical analysis and demonstrate the effectiveness of the proposed compensators and their feasibility for real-time implementation.